Basic Methodological Provisions of Social Synergy at the Present Stage - Medvedeva, Elena; Zakrevskaya, Natalia; Yermilova, Victoria; Chudaev, Mihail; Mayevskaya, Vera (Տիգրան Մեծ)
The article interprets the basic methodological pro-visions of social synergy, giving a deep insight into the theory of self-organizing systems in various spheres. The emphasis is given to the essence and mechanism of transition between order and chaos. The practical value of synergy is also bro-ught to light.
Keywords: Social philosophy